PT-FREE AND EFFICIENT COUNTER ELECTRODE WITH NANOSTRUCTURED MNCO2S4 FOR DYE-SENSITIZED SOLAR CELLS - Suleimenova, Diana; Ibrayeva, Ayagoz; Baptayev, Bakhytzhan; Tashenov, Yerbolat; Balanay, Mannix P. (National Laboratory Astana, 2022)
In the past few years, the development of alternative and renewable energy sources has been one of the urgent and most important tasks due to the growing demand of the population for energy. Dye-sensitized solar cells (DSSC) firstly introduced by Grätzel and O'Regan are third generation photovoltaic devices that have distinctive advantages over silicon solar cells, such as low cost of materials used, ease of fabrication and eco-friendliness.
Keywords: Type of access: Embargo; solar cells